(3oedNU JGQjN GdESdGe ddPgHjs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , J (B833 (3g` s; (3GdPgHj,J (B748 (3g` s ((3eMeO Hf eRjO GdbhLhj s)
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdMhGOK hGdhajGJ CYXe YHQI ddEfSGf s
(3GfJgi ef JdNjUg SfI (B798 (3g` HeOjfI EfWGcjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs